An Analysis of Verbal and Non-Verbal Signs in Nivea Nourishing Body Lotion Advertisemnts - I Dewa Ayu Devi Maharani Santika; Desak Putu Eka Pratiwi; Ni Nyoman Tri Jayanti (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2021)
This study is aimed to analyze the meaning of verbal and non-verbal signs which are found in Nivea Nourishing body lotion Signs are commonly used in advertisements in order to make them attractive and can deliver the messages properly. This research used a qualitative data collection approach and the data source came from YouTube Nivea Body advertising for the Nivea Nourishing body lotion. Saussure's (1983) semiotic theory uses this research issue to evaluate verbal and non-verbal signs and Barthes' (1977) theory of meaning to examine the meaning of verbal and non-verbal signs in advertising for body lotion. 5 verbal signs and 9 nonverbal signs were included in the result. In advertisements, most of these signs contain connotative and denotative meanings, with 1 denotative meaning and 13 connotative meanings identified by the researcher. In all ads, the use of connotative significance is prevalent because advertisers use hidden meanings to communicate messages and encourage buyers to try these goods. Keywords: semiotics, verbal signs, non-verbal signs, advertisements, body lotion, denotative, connotative.